Acute hepatitis after parenteral amiodarone administration. Issue 6 (June 1988) - Pye, M; Northcote, R J; Cobbe, S M
Abstract : Amiodarone is believed to have caused acute hepatitis 24 hours after intravenous administration in two patients in whom no other alternative cause of hepatitis was found.